Translocação de diamidas em soja e milho e efeito sobre Helicoverpa armigera(Hübner, 1808) e Spodoptera frugiperda(J. E. Smith, 1797) - Pes, Maiquel Pizzuti (2019)
Characterization of insecticide movements in plants is important to optimize control efficiency and minimize costs to grower. The present work provided two articles that aims to characterize the mobility of chlorantraniliprole and cyantraniliprole in corn and soybean plants. The first article entitled as "Translocation of chlorantraniliprole and cyantraniliprole applied to seed treatment and leaf spray to control Spodoptera frugiperda (Lepidoptera: Noctuidae)" assessed the movement of chlorantraniliprole and cyantraniliprole applied via seed treatment and foliar spray in maize (VE and V3), to characterize the systemic action of both molecules on the leaves emitted after application. The translocation of both insecticides was quantified in leaf tissues via chromatography technique (LC-MS/MS) and laboratory bioassays with S. frugiperda. Chlorantraniliprole and cyantraniliprole were absorbed and redistributed in the corn plant conferring prolonged residual action with satisfactory control of S. frugiperda. The second article entitled " Anthranilic diamides: an alternative to control of lepidoptera in Bt soybean during flowering?" aimed to evaluate the mobility of chlorantraniliprole and cyantraniliprole in soybean plants after application through seed treatment and foliar spraying. Laboratory bioassays with Helicoverpa armigera and S. eridania and quantification of active ingredients in flower tissues via LC-MS/MS were accomplished. The movement of chlorantraniliprole and cyantraniliprole in soybean plants at different forms of application were evident with the results of caterpillar mortality and quantification of active ingredients in floral tissues. Thus, proving that antranilic diamides are easily translocated and are import for the management of lepidopteran pests that feed on soybean flowers. The physicochemical properties of anthranilic diamides allow the mobility of both insecticides via xylem, however, the form of application and the plant species are determinant for this translocation.